2009
DOI: 10.1108/17465729200900005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring attitudes of the general public to stress, depression and help seeking

Abstract: Many people delay or never seek professional help for stress and depression. There is limited research on this topic using qualitative methodologies, but even less exploring the attitudes of the general population.This study explores the attitudes and preferences of the general population about when and where help is sought for stress and depression through the Somerset Health Panels. These comprised 12 two‐hour panels held across Somerset, England, involving a total of 96 people. This study reveals that a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The above findings are supported in the literature (Coe, 2009;Wegner et al, 2014) indicating that parents seek help by discussing their problem with their close friends and family.…”
Section: My Pillar Of S]strengthsupporting
confidence: 76%
See 1 more Smart Citation
“…The above findings are supported in the literature (Coe, 2009;Wegner et al, 2014) indicating that parents seek help by discussing their problem with their close friends and family.…”
Section: My Pillar Of S]strengthsupporting
confidence: 76%
“…According to Coe (2009), understanding help-seeking attitudes, intentions and behaviours enables health professionals to provide the appropriate services to clients who need psychological support. Nearly all participants indicated that they took the initiative to approach professionals in the rehabilitation centres in order to seek help.…”
Section: Getting Help From Professionalsmentioning
confidence: 99%
“…The development of the concept of two styles was derived through analysis of data collected during the Somerset Health Panels discussion in 2001 on "attitudes to stress, depression and help-seeking" [9]. The Somerset Health Panels were a distinct and established focus group based method of public involvement established in Somerset (South West England) in 1994 to obtain local people's views about health issues [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The Somerset Health Panels were a distinct and established focus group based method of public involvement established in Somerset (South West England) in 1994 to obtain local people's views about health issues [10][11][12]. The importance of disclosure relating to mental health problems is particularly significant as research demonstrates that disclosure is a key barrier to help-seeking [9]. Evidence on the effectiveness of measures to then improve mental health and help-seeking is the focus of much of the mental health literature, although "mental health literacy" is considered by many to be key for both those seeking help and those supporting others to seek help [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although no prior knowledge of participants experiences on any given topic are known, health panels have also been used to tackle sensitive topics, e.g. resuscitation of patients, teenage conception, attitudes and barriers to seeking help for depression and stress related disorders [25]. Although there are regular national surveys [26], there is limited qualitative research published regarding public attitudes to depression and even less on the way in which people self-disclose depression in a public or group situation.…”
Section: Introductionmentioning
confidence: 99%